2014
DOI: 10.1179/2047773214y.0000000157
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of rat model of silicotuberculosis and its pathological characteristic

Abstract: Objective: To establish different stages of silicosis rat model complicated with tuberculosis infection, and compare the pathological characteristics and analyze the impact of silicosis on tuberculosis infection. Methods: SD rats were subjected to intratracheal administration of silica with non-exposure method at the 1st, 30th, or 60th day. At the 50th day, the rats were injected with the suspension of H37Rv (a virulent standard strain of Mycobacterium tuberculosis) via tail-vein. After 40 days post-infection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Silica particles increase intracellular replication of Mycobacterium tuberculosis and release from macrophages [24] . In rat models, defence against Mycobacterium tuberculosis becomes poorer as silicosis progresses [25] . However, silica-induced Th1 responses, with TNF-alpha and IFN-gamma production, should contribute to resistance to, or elimination of, Mycobacterium tuberculosis [26] .…”
Section: Pathophysiologymentioning
confidence: 99%
“…Silica particles increase intracellular replication of Mycobacterium tuberculosis and release from macrophages [24] . In rat models, defence against Mycobacterium tuberculosis becomes poorer as silicosis progresses [25] . However, silica-induced Th1 responses, with TNF-alpha and IFN-gamma production, should contribute to resistance to, or elimination of, Mycobacterium tuberculosis [26] .…”
Section: Pathophysiologymentioning
confidence: 99%
“…Many animal models are used to study M.tb lesions including mice, guinea pigs, rabbits, non-human primates, bovine calves, zebrafish, rats, ferrets, mini pigs, fruit flies, nematodes, planarians, and even amoebas [ 43 – 56 ]. Due to the small size, cost-efficiency, and availability of reagents, mice are widely used and have been crucial for determining immunological requirements that restrict M.tb growth [ 57 , 58 ].…”
Section: Genetic Variation In Mice Controls Necrotizing Responses To mentioning
confidence: 99%
“…This system is a non-invasive instrument that allows animal inhalation of silica particles and may be set to a certain dust concentration. Compared with intratracheal administration of silica dust ( 20 , 21 ), using the dynamic pollution control system facilitated the establishment of an ideal silicosis model. Histopathological observations demonstrated that, following inhalation of SiO 2 for 4 weeks, silicotic nodules containing macrophages developed in the lung tissues of rats.…”
Section: Discussionmentioning
confidence: 99%